Representasi Kapal Selam Indonesia dalam Perspektif Pertahanan Regional - Marsetio, Marsetio; Ritonga, Rajab (Jurnal Kajian Stratejik Ketahanan Nasional, 2018)
Indonesia as one of the centers of gravity in Asia Pacific region requires defence equipment, including submarines as a deterrence effect to play a leadership role within the regional area with all its dynamics in South China Sea. In relation to that role, the Navy is now transformed to meet World Class Navy standards with four elements: (1) excellence in human resources, (2) excellence in technology, (3) organizational excellence, and (4) excellence in operational capabilities. This study tries to find out how submarine representation in the perspective of regional defence is faced with China's overlapping claims in South China Sea, as well as the presence of the United States that seeks to maintain regional hegemony. This research uses a descriptive- explanative method with a qualitative approach based on the constructivist paradigm. The research conclusions are: the existence of submarines as strategic weapons has become a major need for Indonesia to play leadership role in the regional area in facing the intensity of regional political crises as excesses of problems in South China Sea and the emergence of China as a new rival to the United States.